The Implementation of the Problem-Based Learning with TikTok Videos to Enhance Student Learning Outcomes and Activities - Tiara Maulida Afifa, Cut; Agustina, Elita; Widyanto, Anton (Bioilmi: Jurnal Pendidikan, 2024)
A good learning process involves both teachers and students collaboratively. Teacher-centered learning often leads to passive students who tend not to experience engaging learning opportunities. A case study at SMAN 1 Teupah Barat Simeulue indicated that students' learning outcomes in the human digestive system topic were still suboptimal, and students' critical thinking in responding to real-life problems had not yet emerged. This study aims to analyze students' learning outcomes and activities through the implementation of a problem-based learning model assisted by TikTok short video media in the human digestive system topic. The research used a pre-experimental method with a one-group pretest-posttest design, while student activity was measured through observation. Data was collected using test questions and observation sheets. Data analysis was performed with SPSS Version 25 and descriptive statistics. The findings showed that students’ learning outcomes on the human digestive system topic improved significantly, with a p-value of 0.000 < 0.05. Meanwhile, students’ learning activities reached a final score of 66.77%, categorized as good. The application of a problem-based learning model integrated with TikTok video media on the human digestive system topic can enhance students' learning outcomes and activities.